Molecular Insight into Stereoselective ADME Characteristics of C20-24 Epimeric Epoxides of Protopanaxadiol by Docking Analysis - Wenna Guo; Zhiyong Li; Meng Yuan; Geng Chen; Qiao Li; Hui Xu; Xin Yang (Biomolecules, 2020)
Chirality is a common phenomenon, and it is meaningful to explore interactions between stereoselective bio-macromolecules and chiral small molecules with preclinical and clinical significance. Protopanaxadiol-type ginsenosides are main effective ingredients in ginseng and are prone to biotransformation into a pair of ocotillol C20-24 epoxide epimers, namely, (20S,24S)-epoxy-dammarane-3,12,25-triol (24S-PDQ) and (20S,24R)-epoxy dammarane-3,12,25-triol (24R-PDQ) that display stereoselective fate in vivo. However, possible molecular mechanisms involved are still unclear. The present study aimed to investigate stereoselective ADME (absorption, distribution, metabolism and excretion) characteristics of PDQ epimers based on molecular docking analysis of their interaction with some vital proteins responsible for drug disposal. Homology modeling was performed to obtain 3D-structure of the human isoenzyme UGT1A8, while calculation of docking score and binding free energy and ligand−protein interaction pattern analysis were achieved by using the Schrödinger package. Stereoselective interaction was found for both UGT1A8 and CYP3A4, demonstrating that 24S-PDQ was more susceptible to glucuronidation, whereas 24R-PDQ was more prone to oxidation catalyzed by CYP3A4. However, both epimers displayed similarly strong interaction with P-gp, a protein with energy-dependent drug-pump function, suggesting an effect of the dammarane skeleton but not C-24 stereo-configuration. These findings provide an insight into stereo-selectivity of ginsenosides, as well as a support the rational development of ginseng products.